2008
DOI: 10.1071/sr07216
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial leaching from dairy shed effluent applied to a fine sandy loam under irrigated pasture

Abstract: This experiment investigated bacterial transport from land-applied dairy shed effluent (DSE), via field lysimeter studies, using 2 contrasting irrigation methods. Transient water flow and bacterial transport were studied, and the factors controlling faecal coliform (FC) transport are discussed. Two trials (Trial 1, summer; Trial 2, autumn) were carried out, using 6 undisturbed soil monolith lysimeters, 500 mm diameter by 700 mm deep, with a free-draining, Templeton fine sandy loam. DSE with inert chemical trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Studies have shown that leaching of bio-colloids such as E. coli is strongly influenced by soil wetness conditions at the time of animal slurry application as well as the time between slurry application and rainfall occurring after spreading: i.e., the wetter the soil, the higher the leaching of bacteria (43,57). Correspondently, a significant leaching of bacteriophage PRD1 has been observed in connection with rainfall (62).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that leaching of bio-colloids such as E. coli is strongly influenced by soil wetness conditions at the time of animal slurry application as well as the time between slurry application and rainfall occurring after spreading: i.e., the wetter the soil, the higher the leaching of bacteria (43,57). Correspondently, a significant leaching of bacteriophage PRD1 has been observed in connection with rainfall (62).…”
mentioning
confidence: 99%
“…Microbial transport in intact soils has been studied under simulated rain conditions (58,59,65) or with a combination of rainfall and irrigation (43,44), whereas little information is available about microbial transport under natural climate conditions (57,62). Studies have shown that leaching of bio-colloids such as E. coli is strongly influenced by soil wetness conditions at the time of animal slurry application as well as the time between slurry application and rainfall occurring after spreading: i.e., the wetter the soil, the higher the leaching of bacteria (43,57).…”
mentioning
confidence: 99%
“…Preferential flow was reported in earlier lysimeter work McLeod et al, 2001McLeod et al, , 2003McLeod et al, , 2004Pang et al, 2008;Jiang et al, 2008). The transport rate measured in laboratory scale experiments may be considerably lower than the transport rate in the natural environment because the preferential flow pathways allow contaminants to bypass the soil matrix.…”
Section: Discussionmentioning
confidence: 86%
“…Soil depth in these lysimeters ranged from 40 to 100 cm with diameters ranging from 30 to 60 cm (volume ranged from 0.028 to 0.28 m 3 ). Most studies were performed indoors except for the work reported by Jiang et al (2008) and Carlander et al (2000). The focus of their work was on the transport of fecal coliforms, Escherichia coli and salmonella phage from dairy manure or pure cultures.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation